Missed opportunities for institutional delivery and associated factors among urban resident pregnant women in South Tigray Zone, Ethiopia: a community-based follow-up study - Hinsermu Bayu; Girmastion Fisseha; Amlaku Mulat; Gebre Yitayih; Mengistu Wolday (Taylor & Francis Group, 2015)
Background: Every pregnant woman is considered to be at risk and some risks may not always be foreseeable or detectable. Therefore, the presence of a skilled birth attendant at every delivery is considered to be the most critical intervention in reducing maternal mortality and morbidity. In Ethiopia, the proportion of births attended by skilled personnel in urban settings can be as low as 10%. Therefore, the main purpose of this research was to identify factors affecting unplanned home delivery in urban settings, where there is relatively good access in principle to modern healthcare institutions. Design: A community-based follow-up study was conducted from 17 January 2014 to 30 August 2014, among second- and third-trimester pregnant women who had planned for institutional delivery in South Tigray Zone. A systematic sampling technique was used to get a total of 522 study participants. A pre-tested and structured questionnaire was used to collect relevant data. Bivariate and multivariate data analyses were performed using SPSS version 16.0. Results: The study revealed that among 465 pregnant women who planned for institutional delivery, 134 (28.8%) opted out and delivered at their home (missed opportunity). Single women (AOR 2.34, 95% CI 1.17-4.68), illiterate mothers (AOR 6.14, 95% CI 2.20-17.2), absence of antenatal clinic visit for indexed pregnancy (AOR 3.11, 95% CI 1.72-5.61), absence of obstetric complications during the index pregnancy (AOR 2.96, 95% CI 1.47-5.97), poor autonomy (AOR 2.11, 95% CI 1.27-3.49), and absence of birth preparedness and complication readiness (AOR 3.83, 95% CI 2.19-6.70) were significant predictors of unplanned home delivery. Conclusions: A significant proportion of pregnant women missed the opportunity of modern delivery assistance. Educational status, antenatal care status, lack of obstetric complications, poor autonomy, and lack of birth preparedness and complication readiness were among the important predictors of unplanned home delivery.